Post-infectious gastroenterological pathology’s mechanisms in children with rotavirus infection - K. D. Ermolenko; N. V. Gonchar; Yu. V. Lobzin (Журнал инфектологии)
Introduction: Rotavirus infection (RVI) is one of the most common childhood illnesses in countries where routine vaccination against the disease isn`t introduced. The incidence of RVI in Russia remains at a consistently high level, leading to a huge socio-economic damage. In addition, in children who have undergone severe forms of the disease, have high risk of post-infectious functional disorders of the gastrointestinal tract (FD), leading to a decrease in the quality of life and prolonged persistence of dyspeptic phenomena. The pathogenetic mechanisms and factors predisposing to FD in RVI convalescents remain insufficiently studied.The aim of the study was to establish the possible role of intestinal microbiocenosis disorders and immune response in the formation of gastroenterological pathology in children, convalescents of RVI.Material and methods: The work was performed in 2014- 2019. in Pediatric Research and Clinical Center for Infectious Diseases. In the course of the implementation, a comprehensive clinical and laboratory examination was carried out for 60 children aged 1 to 7 years who had suffered RVI in a severe or moderate form, since the onset of infection followed by a three-year follow-up observation. Particular attention was paid to the assessment of intestinal microbiocenosis and immune response in the study group of patients. The interpretation of dyspeptic symptoms in the follow-up period was carried out on the basis of the Rome IV revision criteria. The structure of gastrointestinal tract disorders after rotavirus infection has been established.Results: It was shown that with RVI, persistent changes in the intestinal microbiota are observed, characterized by a decrease in the number of symbiotic Bacteroides thetaiataomicron, Lactobacillus spp. and Faecalibacterium prausnitzii and overgrowth of semipathogenius microorganisms, including Bacteroides fragilis.Conclusion: A close relationship of a number of factors (a decrease in the level of virus-induced production of IFNγ and serum IgA, overgrowth of Proteus spp., Bacteroides fragilis and a decrease in the level of Faecalibacterium prausnitzii and Bacteroides thetaiotaomicron) with the formation of FD in the follow-up period was revealed.